Managing HIV/AIDS in small and medium enterprises (SMEs), with the focus on South Africa : an experience by the International Finance Corporation (IFC), the private sector division of the World Bank Group - Enslin, Laetitia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2007.